Does Time to Initiation of Adjuvant Radiotherapy Affect Reconstruction Outcomes after Endoscopic Resection of Skull Base Malignancies? - Rubino, Franco; Brahimaj, Bledi; Hanna, Ehab Y.; Su, Shirley Y.; Phan, Jack; Grosshans, David R.; DeMonte, Franco; Raza, Shaan M. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction and Objective It is unclear if the length of the time interval to initiation of adjuvant radiation therapy (RT) after endoscopic endonasal surgery affects reconstruction outcomes. In this study we present our experience with adjuvant RT after endoscopic endonasal procedures, to determine if the time to RT after surgery impacts post-RT reconstruction complication rates.Methods A retrospective cohort study of 164 patients who underwent endoscopic endonasal surgery between 1998 and 2021 was conducted. Using Cox proportional hazard ratios (HRs), we evaluated several variables and the complications that occurred during the 1-year period after starting RT.Results Seventy-eight (47.5%) and eighty-six patients (52.5%) received RT before and after the sixth postoperative week, respectively. The overall post-RT complication rates were 28%, most of these were severe infections (n = 20, 12.2%) and delayed CSF leak (n = 4, 2.5%). There was no significant difference in the post-RT complications between the patients who received postoperative RT before or after the sixth operative week (HR: 1.13; 95% confidence interval: 0.63–2.02; p = 0.675). Univariate analysis demonstrated negative impact associated with smoking history (p = 0.015), the use of neoadjuvant chemotherapy (p = 0.0001), and the use of photon therapy (p = 0.012); and we found a positive impact with the use of multilayer reconstruction techniques (overall, p = 0.041; with fat, p = 0.038; and/or fascia graft, p = 0.035). After a multivariate analysis only, smoking history was an independent risk factor for post-RT complications (p = 0.012).Conclusion Delaying RT for more than 6 weeks after endoscopic endonasal surgery does not provide a significant benefit for reconstruction outcomes. However, special attention may be warranted in patients with smoking history who have received neoadjuvant chemotherapy, or in patients who will receive photon-based RT after surgery as these groups were found to have increased complication rates post-RT.
Keywords: endoscopic skull base reconstructions; vascularized flap; radiation therapy; proton therapy; photon therapy